Building an educational-learning program using effective media and its effectiveness in acquiring fourth-primary students of scientific concepts (Journal of the College of Basic Education, 2022)
The current research aims to build an educational-learning program using effective media and its effectiveness in acquiring the fourth primary students of scientific concepts by verifying the following zero hypothesis:1. There is no statistically significant difference at the level (0.05) between the mean scores of the experimental group students who studied in the effective media program and the average scores of the control group students who studied in the usual way in the concept acquisition test.The experimental design was chosen for the two groups, the experimental and the control.